“Impact of Financial Incentives on Performance Of Employees” - RITA KUMARI (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
In enhancing the performance of employees incentives plays a prominent role. Following study depicts the analysis of effect of financial incentives on the performance of employees in organizations. Incentives not only enhances employee’s performance but also helps in the rise of output. Payments which are directly connected to the performance of employees is termed as financial incentives. More the incentives better the performance of employees. Financial incentives acts as an stimulator which encourages the employees to achieve the targeted objectives and goals. One of the most common financial incentive is increment in salary.Present study deals with the review of link present between financial incentives and performance of employees, it also analyzes various types of financial incentives in organization which consists of commission, bonus, sharing of profits etc. Each and every employee are interested to receive some type of incentives, say financial incentives. These incentives boost morale of employees in a very better way. If a company needs to achieve its targeted goals the company must forces focus on the performance of employees which can be enhanced through various ways one of them is by providing financial incentives. Financial incentives not only enhances the performance of employees but along with this also improves productivity, employees loyalty, discipline in organization, better leadership etc. . Financial incentives acts as a signal for employees which shows that their performance are being valued by the organizations which can enhance their satisfaction of job and their organizational commitment. There are various forms in which financial initiatives can be distributed such as commissions, bonuses, increment in the salary commercial in profits etc.. Simple random sampling method has been used and for collecting information from sample, questionnaire survey method has been employed. Working employee has been considered to collect survey. This paper sees the relation between financial incentives and performance of employees in organizations. Finding of this study suggests that in order to enhance performance of employees financial incentives is the best option.